Seasonal Variation Of Helminthic Infestation In Goats In Anand District Of Gujarat - Sharma, Subhash; Patel, P.V.; Choudhary, Dharmendra; Asopa, Shesh; Manohar, Mahendra Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The results of the present study revealed that monsoon season is most favourable for helminth infestation in Goat in Anand District of Gujarat. Trichostrongylus spp was recorded at peak followed by Trichuris spp